Empowering Female Entrepreneurs of 'Aisyiyah Bandung with Digital Marketing Literacy - Arissaputra, Rivaldi; Sentika, Sarah (CV. AFDIFAL MAJU BERKAH, 2023)
The Project on Digital Marketing Training and Assistance for Female Entrepreneurs of 'Aisyiyah in Bandung City has proven to be a transformative initiative. It effectively enhanced the digital marketing strategies of MSMEs entrepreneurs, enabling them to conduct promotions and advertising through social media with efficiency and effectiveness. The program garnered participation from 20 dedicated individuals, all facing challenges in digital promotion. The active involvement, enthusiastic participation, and lively discussions throughout the training and focused group discussion (FGD) sessions demonstrated the commitment of these MSMEs entrepreneurs, particularly those affiliated with 'Aisyiyah. The outcomes and insights gained from the program have provided tangible solutions for the practical implementation of digitalization in their marketing endeavors. To further refine and extend the reach of such activities, future collaboration with external partners is essential. Such collaboration would facilitate the provision of digital literacy support to MSME entrepreneurs, especially in the marketing domain, ultimately boosting their sales revenue. In conclusion, this project program has impacted the digital marketing competencies of 'Aisyiyah Bandung's female MSMEs entrepreneurs. Effective training and support have equipped them to harness the potential of digital platforms for business growth.